Use of contraceptives and associated factors among male adolescents in rural secondary schools, Coast Region, Tanzania: a school-based cross-sectional study - Ally Abdul Lyimo; Jia Guo; Stella Emmanuel Mushy; Beatrice Erastus Mwilike (BMC, 2024)
Abstract Background Teenage pregnancy is still one of the reproductive health concerns facing adolescents in Tanzania. The problem has been associated with physiological, psychological, and social changes and increases the risk of unsafe abortion and adverse maternal, fetal, and neonatal outcomes among adolescents. Low utilization of contraceptive methods among adolescents is one of the key causes. The strategy of involving male adolescents in sexual and reproductive health programs can increase the rate of contraceptive use among adolescents, thereby preventing teenage pregnancy. Objective To examine factors associated with the uptake of contraceptives among male secondary school adolescent students. Methods This was a cross-sectional study conducted in rural secondary schools in Kisarawe District, Coast Region, Tanzania. Multi-stage sampling methods were used to recruit participants. Descriptive and multiple regression analyses were conducted to assess the prevalence and factors associated with contraceptive use. 95% confidence interval and p-value < 0.05 were considered statistical significance. Univariate and multivariate logistic regression were tested for the Crude Odds Ratio (COR) and Adjusted Odds Ratio (AOR) respectively. Results The study involved 422 male students with the majority of them 58.1% aged 17-19 years, 50.2% were Muslim, 76.3% were studying in government schools, 62.3% were from households size of 4-6 members, 87.4% were not in a relationship, and 64.2% were living with both parents. Less than half (38.9%) of male students reported ever having sex in their lifetime, and among them, very few (29.8%) used any method of contraceptive. The reported lowest age for the first sex was 10 years. The male condom was the most method used (69.4%) and Pharmacy/Chemist Shops were the common source of contraceptive services (55.1%). Students who had adequate knowledge of contraceptives were more likely to report the use of contraceptive methods compared to those who had inadequate knowledge (AOR = 2.704, 95% CI: 1.220-5.995, p = 0.014). Participants in Private schools were 4.3 times more likely to report the use of contraceptives than those in government schools (AOR = 4.347, 95% CI: 1.758-10.762, p = 0.01). Students in a relationship were 3.5 times more likely than those not in a relationship to report the use of a contraceptive method (AOR = 3.51, 95% CI: 1.421-8.670, p = 0.006). Conclusion The study found the low use of contraceptives among male adolescents who ever had sex in their lifetime. Thus, it's suggested that age-tailored comprehensive sexual and reproductive health education should start to be taught from a very young age as adolescents initiate sex at an early age. Also, Teenage pregnancy prevention programs should involve males as the key players during the development and implementation of the program as most of the decisions among partners are from men.